The ANALISIS KEANDALAN CONVEYOR BELT DI AREA NPK2 PT. X BERDASARKAN DATA KERUSAKAN DAN WAKTU OPERASI - M.Zakarsyi Lilma Abid; Alviani Hesthi Permata Ningtyas; Ajeng Tri Rahayu (Universitas Muhammadiyah Gresik, 2025)
Conveyor systems play an important role in supporting material handling processes in the fertilizer industry. Continuous operation under high workloads can lead to component wear, increased failure frequency, and downtime that disrupts production continuity. These conditions highlight the need for reliability evaluation to ensure optimal conveyor performance. This research analyzes the reliability of the conveyor system at NPK Plant 2 of PT. X using historical maintenance data collected from July 2024 to June 2025. The analysis was conducted using reliability parameters, including Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), Availability, Failure Rate, and Reliability. In addition, Failure Mode and Effect Analysis (FMEA) was applied to identify critical components and determine maintenance priorities based on the Risk Priority Number (RPN). The results indicate that most conveyor units exhibit high availability and reliability; however, several units still experience relatively high downtime and repair duration. The conveyor belt component shows the highest RPN value and therefore requires priority attention in maintenance activities. Implementing more effective preventive maintenance and enhanced monitoring of critical components is expected to reduce downtime and improve the reliability and operational efficiency of the conveyor system.